Schwindel bei kardiologischen Erkrankungen - Jilek, Clemens; Lewalter, Thorsten (DMW - Deutsche Medizinische Wochenschrift, 2019)
Dizziness is a symptom that may be of cardiac origin. Diagnosis and treatment of cardiac diseases is of important prognostic impact. Dizziness may be caused due to two different cardiac disorders: (1) as symptom of a cardioembolic event or (2) as a symptom of a low cardiac output leading to an intermittent global cerebral hypoperfusion. This review article presents diagnostic as well as therapeutic pathways in a comprehensive tabular overview.
Keywords: Schwindel; Herzerkrankung; Diagnostik; Therapie